Hipertensão arterial e fatores associados em adultos residente em municípios da Amazônia Legal - Silva, Elcimary Cristina (2014)
Hypertension in adults is a serious public health problem due to its high prevalence and low levels of control, with very important contributions at causes of morbidity and cardiovascular mortality. Objective: To analyze the prevalence of hypertension and associated factors in in men and women adults population living in municipalities of Amazonia Legal. Methods: A population-based cross sectional study was conducted in cities of Amazonia Legal. Socio-demographic, lifestyle, anthropometric data were collected and blood pressure was measured, being considered hypertensive individuals who had systolic blood pressure ≥ 140 mmHg and diastolic blood pressure ≥ 90 mmHg and those who reported use of antihypertensive drugs. Statistical analyzes were performed using the “svy” prefix in Stata version 11.0. Results: The prevalence of hypertension was 22.31%. After adjusting the variables associated with hypertension in men were age in age group 30–39 years [RPadjusted=2,69; IC95% 1,49–4,86], 40–49 years [RPadjusted=3,28; IC95% 1,82–5,93] e 50–59 years [RPadjusted=4,80; IC95% 2,63–8,76], overweight [RPadjusted=1,97; IC95% 1,39–2,78], obesity [RPadjusted=3,32; IC95% 2,32–4,75] and being born in the North or Northeast region[RPadjusted=0,31; IC95% 0,18–0,59]. Among women, they were associated with SAH in the age group 30-39 years [RPadjusted=1,52; IC95% 0,78–2,96], 40–49 years [RPadjusted=3,41; IC95% 1,91–6,07] e 50–59 years[RPadjusted=7,29; IC95% 4,07–13,07]; and wine consumption [RPadjusted=0,31; IC95% 0,10–0,97] and obesity 2,39; IC95% 1,65–3,45]. Conclusion: Hypertension was independently associated with age, nutritional status and naturalness in men. In women, the variables associated with hypertension were age, nutritional status and type of alcoholic beverage.